Supramolecular interaction of 2,4-dichlorophenol and beta-cyclodextrin functionalized ionic liquid and its preliminary study in sensor application - Mohamad, S.; Chandrasekaram, K.; Rasdi, F.L.M.; Manan, N.S.A.; Raoov, M.; Sidek, N.; Fathullah, S.F. (2015)
The supramolecular interaction of 2,4-dichlorophenol (2,4-DCP) and beta-cyclodextrin fiinctionalized ionic liquid, a mono-6-deoxy-6-(3-benzylimidazolium)-beta-cyclodextrintosylate (beta-CD-BIMOTs) has been investigated. The inclusion complex of beta-CD-BIMOTs-2,4-DCP complex was analyzed with conventional spectroscopic techniques and compared with native beta-CD-2,4-DCP complex. The mechanism of the inclusion too was studied and discussed based on FTIR, H-1 NMR and 2D NOESY analysis. beta-CD-BIMOTs has a stronger binding affinity towards 2,4-DCP compared to native beta-CD based on the formation constant value calculated. In this work, modified electrodes were fabricated by mixing beta-CD-BIMOTs and carbon paste electrode (CPE) for determination of 2,4-DCP. The electrochemical behavior of 2,4-DCP at beta CD-BIMOT5/CPE exhibits higher electrochemical performance than that of native beta-CD/CPE and CPE, revealing that CPE modified beta-CD-BIMOTs not only displays good electrical properties of the ionic liquid but also exhibits high supramolecular recognition properties of beta-CD-BIMOTs through the formation of an inclusion complex between beta-CD-BIMOTs and 2,4-DCP molecules. This preliminarily study shows that beta-CD-BIMOTs can act as an inexpensive electrochemical sensor that is suitable for the determination of 2,4-DCP. (C) 2015 Elsevier B.V. All rights reserved.